Herre, rör mig med ditt ord - Liljendal kyrkokör; Huotilainen, Santtu; Malmberg, Leif; Pentti, Hannu; Silfvast, Anne; Silfvast, Kaj; Jokinen, Antti (Liljendal kyrkokör, 2003)
21 kappaletta.
Keywords: kirkkokuorot